Laboratory-Scale Single Axis Solar Tracking System: Design and Implementation - Allan Soon Chan Roong; Shin-Horng Chong (International Journal of Power Electronics and Drive Systems (IJPEDS), 2016)
This paper presents the design and development of a laboratory-scale single axis solar tracking system. The chronological method was implemented into the system because it has high accuracy and can save more energy as compared to other types of solar tracking system. The laboratory-scale single axis solar tracking system can be used to identify the suitable and safe workspace for the installation of the actual solar tracking system plant. Besides, the validity of the laboratory-scale single axis solar tracking system was examined experimentally. The angle of rotation, per hour is preferable to be implemented into the designed laboratory-scale single axis sun tracking system due to the high performance ratio which is 0.83 and can save the energy up to 25% during sunny days.